PENGARUH AKTIVITAS BELAJAR DAN KEMANDIRIAN DALAM MENGERJAKAN TUGAS TERHADAP HASIL BELAJAR SISWA EKONOMI KELAS XI DI SMA SEMEN PADANG (JURNAL ECONOMICA : Research of Economic And Economic Education, 2014)
AbstractThis study aims to examine) The effect of learning activities and independence  in doing tasks on learning outcomes of students in high school economics class XI Semen  Padang.When the study was conducted in May 2014The results showed that: 1) There is a positive and significant effect of learning activities on student learning outcomes in high school economics class XI  Semen  Padang  this  with  tcount>t  table   (4.955>  1.661).  2)  in  positive  and significant impact of independence in doing the learning outcomes of students in high school economics class XI Semen Padang this is evidenced by the value of tcount>ttable   (7.556>  1.661),  there  is  a  positive  and  significant  impact  jointly between  learning  activities  and  independence   in  the  tasks  of  the  learning outcomes of students in high school economics class XI Semen Padang academic year 2013/2014 this is evidenced by the Fcount>Ftable (135.599>3.09) and R Square0.745.